Fortified milo for gestating sows - Allee, G.L.; Koch, B.A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Forty sows (Yorkshire, Hampshire, and Duroc) were used to study effects of feeding a milo diet fortified with vitamins and minerals (FM) to bred sows from approximately 25 days after breeding to 10 days before farrowing. The sows were fed in this manner for three gestation periods. Control sows received a balanced milo-soybean meal diet (MSB) throughout gestation.
Swine Industry Day 1972 is known as Swine Day 1972
Keywords: Swine; Fortified milo; Gestation; Sows